Analisis Rasio Modal Kerja di PT Bank Pembangunan Daerah Jawa Timur Tbk - Fiorentina Amanda Argawandani; Daya Amarta Suwarjana; Olga Fatmah Rahmawati; Renny Oktafia (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The objective of this study is to examine the working capital ratio of PT Bank Pembangunan Daerah Jawa Timur Tbk from 2020 to 2022. The working capital ratio serves as a vital measure to evaluate the financial well-being of a company and its capacity to fulfill short-term commitments. This investigation employs a descriptive analytical approach, gathering financial data from the annual financial reports of PT Bank Pembangunan Daerah Jawa Timur Tbk. The data collected is then analyzed using various relevant working capital ratios. The results of this analysis provide an overview of the efficiency of the company's working capital management, as well as potential risks or opportunities that can be identified from the financial aspect. It is hoped that the findings from this research can contribute to further understanding of the financial health of PT Bank Pembangunan Daerah Jawa Timur Tbk and provide insight for decision makers regarding working capital management strategies in the future.